Manajemen Wildlife Hazard di Aerodrome Sultan Aji Muhammad Sulaiman Sepinggan Balikpapan - Carolina, Rahel Angela; Saputra, Surya Tri; Akbar, Muhammad Caesar (Politeknik Penerbangan Indonesia Curug, 2024)
Aviation safety is an important part in the world of aviation. One form of aviation safety is preventive and mitigating actions in the event of unwanted things such as a wildlife hazard. Sultan Aji Muhammad Sulaiman Sepinggan Airport, Balikpapan is an airport that has a strategic geographical position, namely the presence of forests and the sea in the south and west areas. This geographical location is the main trigger for the entry of wild animals and bird attacks at the Sepinggan aerodrome, Balikpapan. The method used in this research is descriptive qualitative. The conclusion that can be drawn from this research is the need for short-term and long-term actions such as checking by personnel who have received special training, coordinating with related units, and compiling and producing report data according to a predetermined format.